Thermal stability and enhanced thermoelectric properties of the tetragonal tungsten bronzes Nb8−xW9+xO47 (0 < x < 5). Issue 20 (5th May 2017) - Cerretti, G.; Schrade, M.; Song, X.; Balke, B.; Lu, H.; Weidner, T.; Lieberwirth, I.; Panthöfer, M.; Norby, T.; Tremel, W.
Abstract : Engineering of nanoscaled structures allows to control the electrical and thermal transport in solids for thermoelectric applications where a combination of low thermal conductivity and low electrical resistivity is required. Abstract : Thermoelectric materials are believed to play a fundamental role in the energy field over the next years thanks to their ability of directly converting heat into usable electric energy. To increase their integration in the commercial markets, improvements of the efficiencies are needed. At the same time, cheap and non-toxic materials are required along with easily upscalable production cycles. Compounds of the tetragonal tungsten bronze (TTB) series Nb8− x W9+ x O47 fulfill all these requirements and are promising materials. Their adaptive structure ensures glass-like values of the thermal conductivity, and the substitution on the cation side allows a controlled manipulation of the electronic properties. In this contribution we report the stability study of the two highly substituted samples of the series, Nb5 W12 O47 ( x = 3) and Nb4 W13 O47 ( x = 4), when subjected to thermal cycling. Moreover, we show the results of the thermoelectric characterization of these samples. The two compounds have not been affected by the thermal treatment and showed an improvement of the thermoelectric performances up to a zT = 0.2 above 1000 K.